Higher order thinking skills competencies required by outcomes-based education from learners - MM Chabeli (AOSIS, 2006)
Outcomes-Based Education (OBE) brought about a significant paradigm shift in the education and training of learners in South Africa. OBE requires a shift from focusing on the teacher input (instruction offerings or syllabuses expressed in terms of content), to focusing on learner outcomes. OBE is moving away from 'transmission' models to constructivistic, learner-centered models that put emphasis on learning as an active process (Nieburh, 1996:30). Teachers act as facilitators and mediators of learning (Norms and Standards, Government Gazette vol 415, no 20844 of 2000). Facilitators are responsible to create the environment that is conducive for learners to construct their own knowledge, skills and values through interaction (Peters, 2000). The first critical cross-field outcome accepted by the South African Qualification Framework (SAQA) is that learners should be able to identify and solve problems by using critical and creative thinking skills. This paper seeks to explore some higher order thinking skills competencies required by OBE from learners such as critical thinking, reflective thinking, creative thinking, dialogic / dialectic thinking, decision making, problem solving and emotional intelligence and their implications in facilitating teaching and learning from the theoretical perspective. The philosophical underpinning of these higher order thinking skills is described to give direction to the study. It is recommended that a study focusing on the assessment of these intellectual concepts be made. The study may be qualitative, quantitative or mixed methods in nature (Creswell 2005).